Harmoni antara umat beragama di Indonesia: Kajian perbandingan kerukunan umat Islam dan Hindu di Bali dan Jawa Timur / Mohamad Ali Hisyam - Mohamad Ali , Hisyam (2017)
As a nation, Indonesia remarkably represents religious diversity and multicultural society. This phenomenon entails harmony among religions, to create peaceful life among society. In this research, I attempt to explain harmony between Hindus and Muslim in Bali and East Java. It is interesting to portray Hindus-Muslim relationship, because, compared with Muslim’s relation to other Semitic believers in Indonesia, they have been living together without any conflicts or any religious tensions. This research takes Bali and East Java as object of the research at least because of two reasons. First, Bali symbolizes a center of multicultural society and interfaith harmony with the majority of Hindus, and second, East Java is well known as Islamic-identity-based province with the majority of Muslim. Both areas are comparatively fascinating. In Bali, this research was located in Kampung Sindu Karangasem and Kampung Gelgel Klungkung, while in East Java it was located in Desa Sedaeng Tengger Pasuruan and Desa Balum Lamongan. Since it is religious and sociological study, this research uses phenomenological approach and qualitative method for analyzing data. It explores data (literal and empirical) analytically, comparatively, and descriptively. In doing so, this research applies symbolic interaction theory, social dominant orientation, and structural functionalism, by linking literary research, in-depth interview, and field observation. This research aims to answer three questions: (1) how is the process and the dynamic of harmonious life between Hindus and Muslim in Bali and East Java; (2) how is the impact of minority and majority relationship in the process of building harmony; and (3) how is the harmonious model of Hindus and Muslim harmony in Bali and East Java. Findings of this research conclude that Hindus and Muslim society, on their process of building interreligious relationship, were inherently influenced by social culture, tradition, and local wisdom. There are several factors which approve Hindus-Muslim relationship in a certain place to be unique and distinctive. Otherwise, this research assumes that in general the process of interreligious harmony in Bali and East Java was attained in harmony: Hindus and Muslim society have relatively interacted each other without any conflicts. They constructed this harmonious relationship through symbolic communication within social, cultural and traditional accounts. They have inadmissibly evaded majority-minority relation to narrow cultural gaps and strengthen religious brotherhood among them. Indeed, diversity and plurality have become social characters that enhance interreligious harmony. This research ends with at least three models of interreligious relationship: traditional, conflict reconciliation, and participatory model.